The role of Chinese herbal medicine in the treatment of diabetic nephropathy by regulating endoplasmic reticulum stress - Wei, Maoying; Liu, Xingxing; Li, Mingdi; Tian, Xiaochan; Feng, Mingyue; Pang, Boxian; Fang, Zeyang; Wei, Junping (Frontiers in Pharmacology, 2023)
Diabetic nephropathy (DN), a prevalent microvascular complication of diabetes mellitus, is the primary contributor to end-stage renal disease in developed countries.Existing clinical interventions for DN encompass lifestyle modifications, blood glucose regulation, blood pressure reduction, lipid management, and avoidance of nephrotoxic medications. Despite these measures, a significant number of patients progress to end-stage renal disease, underscoring the need for additional therapeutic strategies. The endoplasmic reticulum (ER) stress response, a cellular defense mechanism in eukaryotic cells, has been implicated in DN pathogenesis. Moderate ER stress can enhance cell survival, whereas severe or prolonged ER stress may trigger apoptosis. As such, the role of ER stress in DN presents a potential avenue for therapeutic modulation. Chinese herbal medicine, a staple in Chinese healthcare, has emerged as a promising intervention for DN. Existing research suggests that some herbal remedies may confer renoprotective benefits through the modulation of ER stress. This review explores the involvement of ER stress in the pathogenesis of DN and the advancements in Chinese herbal medicine for ER stress regulation, aiming to inspire new clinical strategies for the prevention and management of DN.